2021
DOI: 10.1002/ece3.7175
|View full text |Cite
|
Sign up to set email alerts
|

Age‐ and sex‐related dietary specialization facilitate seasonal resource partitioning in a migratory shorebird

Abstract: Dietary specialization is common in animals and has important implications for individual fitness, inter‐ and intraspecific competition, and the adaptive potential of a species. Diet composition can be influenced by age‐ and sex‐related factors including an individual's morphology, social status, and acquired skills; however, specialization may only be necessary when competition is intensified by high population densities or increased energetic demands. To better understand the role of age‐ and sex‐related die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 86 publications
(119 reference statements)
0
11
0
Order By: Relevance
“…Video recordings confirmed that sandpipers ingest biofilm, and parallel studies using stomach samples and stable isotopes revealed that biofilm can account for approximately 45-59% of the total diet or 50% of the daily energy budget of western sandpipers (Kuwae et al, 2008). Reliance on biofilm differs among age classes and sexes of small-bodied shorebirds and can be up to 70% of the total diet (Hall et al, 2021;. Bristle distribution and length differences between shorebird species likely reflect functional morphological adaptations to remove biofilm.…”
Section: Shorebird Foragingmentioning
confidence: 70%
“…Video recordings confirmed that sandpipers ingest biofilm, and parallel studies using stomach samples and stable isotopes revealed that biofilm can account for approximately 45-59% of the total diet or 50% of the daily energy budget of western sandpipers (Kuwae et al, 2008). Reliance on biofilm differs among age classes and sexes of small-bodied shorebirds and can be up to 70% of the total diet (Hall et al, 2021;. Bristle distribution and length differences between shorebird species likely reflect functional morphological adaptations to remove biofilm.…”
Section: Shorebird Foragingmentioning
confidence: 70%
“… Beninger et al (2011) used δ 13 C and δ 15 N measurements of stomach contents, liver and muscle tissue of spring staging western sandpipers at our study site and, by contrasting isotopic mixing model predictions based on these assumed differing periods of dietary integration, predicted a downward shift in trophic position during migration (see also Hall et al , 2021 ). Although we generally agree that these different tissues and components clearly represent different periods of integration with muscle almost certainly reflecting diet prior to arrival at our site, the absence of ground-truthed isotopic baseline data along the flyway and the lack of knowledge of individual movement history remain problematic.…”
Section: Discussionmentioning
confidence: 99%
“…To move forward, studies at key stopover and wintering sites along the flyway (e.g. studies quoted here for the Fraser estuary; Hall et al, 2021 , for San Francisco Bay) that establish tissue isotope values of birds in isotopic equilibrium with local food webs are needed.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of Calidris mauri (western sandpiper) in North America during spring, epifaunal invertebrates made up a higher proportion of the diets of males, which were lighter in weight and had shorter bills than females, while polychaetes dominated the diets of adult females, which had longer bill lengths (Hall et al, 2021). In T. totanus, subordinate individuals were also excluded from preferred feeding areas and were forced to feed on alternative prey (Cresswell, 1994).…”
Section: Intraspecific Variations In Dietary Compositionsmentioning
confidence: 99%
“…These adaptive variations facilitate their dietary segregation through one or multiple aspects, including their different choices on target prey, foraging habitats, and migration or foraging time (Catry et al, 2014). Within some shorebird species, conspecifics can even differentiate their diets between sexes or age groups to reduce intraspecific competition by targeting either different prey species or different sizes of the same prey species (Hall et al, 2021). However, despite the findings from these studies, the dietary spectra and niche dynamics of shorebirds occurring in Asia are still very poorly understood (Hua et al, 2015).…”
Section: Introductionmentioning
confidence: 99%